Redesain Sistem Akuntansi Penerimaan Kas Pada Usaha Kecil Menengah Tahu Takwa Dung Tak Tong - Binti Fatimatuz Zahrok; Dianita Meirini (Politeknik Ganesha Medan, 2022)
In the operation of small and medium businesses, Tahu Takwa Dung Tak Tong is inseparable from cash inflow transactions. In the operation, obstacles were found in the form of a difference between physical cash and cash in the cash register. In addition, the task of recording cash with cash holders is controlled by the same person. This can weaken internal control. The purpose of this research is to design an improvement in the cash receipts accounting system especially the recording of cash receipts and to find out how to apply the cash receipts accounting designed system in the Tahu Takwa Dung Tak Tong small and medium enterprises and to find out how to apply the cash receipts accounting system design to the Tahu Takwa Dung Tak Tong small and medium enterprises. The used research approach is qualitative research methods. The result of this study are finding error oints and multiple functions in the implemented system. The results of this study are found error points and found multiple functions in the system that has been implemented. The conclusion of the research is the improvement of the cash receipts accounting system and the separation of functions in the cash receipts system. With the improvement of the system as proposed, it aims to strengthen the internal control and is also useful in terms of saving the assets of these small and medium enterprises.